The effectiveness of brushing the teeth using two shapes of toothbrush - Riyanti, Eriska; Andisetyanto, Prima; Pratidina, Naninda Berliana; Primarti, Risti Saptarini; Andiesta, Niekla Survia (Padjadjaran Journal of Dentistry, 2021)
Introduction: Dental and oral health or cleanliness is one indicator to measure the effectiveness of brushing teeth, particularly concerning the type and shape of toothbrush and the way of brushing teeth. The aim of the study was to find out the effectiveness of plaque index decrease before and after brushing teeth using two different types of the toothbrush.  Methods: The investigation was carried out using single-blind and parallel quasi-experimental methods.  The sample comprises 30 people from Bandung City aged between 6 – 7 years old, selected through purposive sampling.  The subjects were directly categorized into two groups of treatment.  Patient Hygiene Performance Modification (PHP-M) used to measure the amount of plaque. Results: The data were analyzed using paired t-test and independent t-test.  The straight-handled toothbrush yielded a score of 11.967 in the paired t-test.  This score is higher than the t-table (t = 2.160; p < 0.05), which meant that the H0 is rejected.  The angled-handled toothbrush had a score of 7.385 in the paired t-test.  The score is higher than the t-table (t = 2.131; p < 0.05), which meant that the H0 is rejected.  The statistical analysis using independent t-test yielded a score of 1.814, which was lower than the t-table (t = 2.048; p > 0.05). Thus, meaning that the H0 is accepted. Conclusion: It was concluded that there is no difference in the plaque index before and after brushing teeth using the two types of the toothbrush.